Type specimen of Oreomyrrhis borneensis Merr. (Apiaceae) unearthed in Herbarium of National Museum of Philippines (PNH) - Chung, Kuo-Fang (Phytotaxa, 2013)
During his post as a botanist with Bureau of Science, Manila, E. D. Merrill described Oreomyrrhis borneensis Merrill (1918: 514) based on specimens collected in a joint expedition by Joseph and Mary Strong Clemens (Clemens 10622) and D. Le Roy Topping (Topping 1687) to Mount Kinabalu, Borneo. Merrill (1918) designated Clemens 10622 as type [‘Mrs. Clemens 10622 (type)’] but without stating the institution where the type was preserved. Merrill also cited Topping 1687, but not as a type, thus it was a paratype (McNeill et al. 2012: Art. 9.6). In revising Oreomyrrhis Endlicher (1839: 787), Mathias & Constance (1955) designated the collection of Clemens 10622 at UC as ‘UC-type’ without any comment. This treatment was followed by Beaman et al. (2001; ‘holotype UC n.v.’) and the subsequent study by Chung (2007) where Oreomyrrhis was further synonymized under Chaerophyllum Linnaeus (1753: 258–259) because the former taxon was shown derived from within the latter in phylogenetic analyses (Chung et al. 2005, Chung 2007). The UC-type (http://plants.jstor.org/specimen/uc214731), however, is tagged as ‘unspecified type’ in the website of The University and Jepson Herbaria (http://ucjeps.berkeley.edu/cgi-bin/gtt.pl?gtt=UC214731).